2013
DOI: 10.1016/j.ajhg.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Germline PIK3CA and AKT1 Mutations in Cowden and Cowden-like Syndromes

Abstract: Cowden syndrome (CS) is a difficult-to-recognize multiple hamartoma syndrome with high risks of breast, thyroid, and other cancers. Germline mutations in PTEN on 10q23 were found to cause 85% of CS when accrued from tertiary academic centers, but prospective accrual from the community over the last 12 years has revealed a 25% PTEN mutation frequency. PTEN is the phosphatase that has been implicated in a heritable cancer syndrome and subsequently in multiple sporadic cancers and developmental processes. PTEN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(115 citation statements)
references
References 22 publications
(18 reference statements)
0
108
0
5
Order By: Relevance
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…For instance, the inherited disease Cowden syndrome/multiple hamartoma syndrome is caused by either germline heterozygous inactivating mutations in the PtdIns(3,4,5)P 3 phosphatase PTEN (OMIM #158350, CWS1), or germline activating mutations or amplifi cations of the PtdIns(3,4,5)P 3 -synthesizing enzyme PIK3CA (OMIM #615108, CWS5; ref. 7 ). Patients with Cowden syndrome show a predisposition to developing breast, thyroid, and endometrial cancers, and about 70% of these individuals have benign thyroid abnormalities, such as multinodular goiter, adenomatous nodules, and follicular adenoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 Of note, mosaic mutations of these genes cause CLOVES 17 and Proteus syndrome, 18 respectively. Because Sanger sequencing is still the mainstay of clinical genetic testing, it is likely that many patients with low-level mosaicism in the peripheral blood remain undiagnosed.…”
Section: Discussionmentioning
confidence: 99%